Effect of Digestrom® and Poultry Star® on the Body Performance and Immunity Status of Broiler Chickens - Abdulhasan D. , Sahar (International Journal of Poultry Science, 2018)
Objective: This study was carried out to evaluate the positive effects of two different commercial products (Digestrom® and Poultry Star®) on body performance and the immune response against Newcastle disease after challenge with a virulent local strain in broiler chickens routinely vaccinated against Newcastle disease. Materials and Methods: A total of 250 one-day-old broiler chicks were randomly distributed to five groups (G1-G5) with 50 chicks per group and treated as follows, G1: Received Digestrom® as a feed additive at a dose of 150 mg kg–1, G2: Received Poultry Star® as a feed additive at a dose of 0.5 g kg–1 (2×1011 CFU kg–1), G3: Received Digestrom® at a dose of 150 mg kg–1 and Poultry Star® at a dose of 0.5 g kg–1 (2×1011 CFU kg–1) as feed additives, G4: Positive control (vaccinated but not treated), G5: Negative control (vaccinated and treated). All groups except G5 (negative control) were vaccinated with NDV LaSota and 14-days-old IBDV D78 intermediate at 5, 10 and 20 days of age via drinking water. At the age of 25 days, all groups were challenged with the virulent strain of Newcastle disease at 100 ELD50 106. Results: The current study showed the highest variable antibody titer (Abs) in the third group that was fed Digestrom® and Poultry Star® with significant increases (p<0.05) in serum total protein, albumin and globulin levels, average daily feed intake and average daily gain (p<0.05) as well as a significant decrease (p<0.05) in morbidity and mortality, followed by the other groups (G1 and G2) that were fed with one product, compared to the positive control group (G4). Meanwhile, the results were significantly lower in the negative control group (G5) than in all other groups. The results following challenge with virulent NDV were very high in G5 and very low in G3. Conclusion: Dietary inclusion of 150 ppm Digestrom® improved body performance, which led to increased serum total protein levels. Moreover, both individual and combined application of Digestrom® and Poultry Star® increased the immune response against NDV, with synergistic effects observed with combined treatment.